Strategi Manajemen Kesiswaan Dalam Memotivasi Untuk Membentuk Karakter Siswa (Studi Kasus di Madrasah Tsanawiyah Negeri 1 Lombok Tengah) - Sunardi; Adipta, Marzaenal (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of this research is analyze application and implication student management strategy in motivational to shape student character (study cases in MTsN 1 Lombok Tengah). The Method in this research is qualitatif method. Data collected from interviews, observations and documentation.  Researcher try to analyze application and implication strategic of vice head of student field in motivational to shape student character. The result show that application student management strategy in motivating to shape student character that done by vice head of student field throught apply function of management  that well by starting from planning by make work program, then organizationing for shaping and coordination with all guide of extraculiculer in madrasa. Then implementation with carry out work program that arranged before by each duty of guide together. The last is monitoring that apply evaluation intensively and periodicly of work program and continously coordinance with guide and other vice head to reach the goal that clearly. After that implication student management strategy in motivating to shape student character by work program that implicate to madrasa especially student. Student commonly growing own talent and own interest by many guidiance activity in madrasa and get achievement in each own field. Student commonly get attention that similar by teacher especially student guider  field  for smoothness and the succes of learning in madrasa.